FACTORS INFLUENCING LAW ENFORCEMENT AGAINST ILLEGAL SAND MINING ACTIVITIES (C EXCAVATION) CARRIED OUT BY VILLAGE HEADS IN KIKIM DISTRICT, LAHAT DISTRICT - Kirana, Chandra; Suharyono, Suharyono (Universitas Muhammadiyah Sumatera Utara, 2025)
The Indonesian state is based on the 1945 Constitution of the Republic of Indonesia which emphasizes that the Indonesian state is not only based on power (power state) but also based on law (rule of law). Indonesia is a country with natural resources in the form of coal and minerals. However, the activities carried out by the community sometimes violate the law because mining is carried out without permits or illegal mining. The research method used is empirical juridical. The formulation of the problem studied and analyzed is the factors that influence law enforcement against illegal sand mining activities (excavating c) carried out by village heads in the Kikim district, Lahat district. The result is the legal factor itself. There is no legal umbrella that gives permanent legal power to the police to control illegal mining practices. Second, the Law Enforcement Factor, namely the lack of socialization of law enforcement, is a factor causing the rise in illegal sand mining crimes. Weak supervision and law enforcement give the impression of giving freedom and not deterring illegal sand mining perpetrators